The relationship between cytokine and neutrophil gene network distinguishes SARS-CoV-2-infected patients by sex and age - Freire, Paula P.; Marques, Alexandre H. C.; Baiocchi, Gabriela C.; Schimke, Lena F.; Fonseca, Dennyson L. M.; Salgado, Ranieri C.; Filgueiras, Igor S.; Napoleao, Sarah M. S.; Placa, Desiree R.; Akashi, Karen T.; Crespo Hirata, Thiago Dominguez; El Khawanky, Nadia; et al. (Amer Soc Clinical Investigation Inc, 2021)
The fact that the COVID-19 fatality rate varies by sex and age is poorly understood. Notably, the outcome of SARS-CoV-2 infections mostly depends on the control of cytokine storm and the increasingly recognized pathological role of uncontrolled neutrophil activation. Here, we used an integrative approach with publicly available RNA-Seq data sets of nasopharyngeal swabs and peripheral blood leukocytes from patients with SARS-CoV-2, according to sex and age. Female and young patients infected by SARS-CoV-2 exhibited a larger number of differentially expressed genes (DEGs) compared with male and elderly patients, indicating a stronger immune modulation. Among them, we found an association between upregulated cytokine/chemokine- and downregulated neutrophil-related DEGs. This was correlated with a closer relationship between female and young subjects, while the relationship between male and elderly patients was closer still. The association between these cytokine/chemokines and neutrophil DEGs is marked by a strongly correlated interferome network. Here, female patients exhibited reduced transcriptional levels of key proinflammatory/neutrophil-related genes, such as CXCL8 receptors (CXCR1 and CXCR2), IL-1 beta, S100A9, ITGAM, and DBNL, compared with male patients. These genes are well known to be protective against inflammatory damage. Therefore, our work suggests specific immune-regulatory pathways associated with sex and age of patients infected with SARS-CoV-2 and provides a possible association between inverse modulation of cytokine/chemokine and neutrophil transcriptional signatures.